Banana grading system using color histogram (BGS) - Siti Nur Saadah, Mohd Jali (2012)
Bananas Grading System (BGS) which is one of the system using image processing technique.The purpose of BGS is used to standardize the grading of the banana and distinguish between three differences classes of banana which are unripe,ripe and overripe.This BGS used computer system to analyze and interprets images that correspondent to human eye and mind.This study is taken into account of four types of banana fruits which are ‘Pisang Lemak Manis’,‘Pisang Mas’,‘Pisang Putar’ and ‘Pisang Berangan’.It attempts to form the decision by analysing the skin colour and condition.Bananas Grading System (BGS) is been done manually which brings variation of the results for banana grading. Since the colour is one of the most significant criteria related to fruit identification and fruit quality,it is a good indicator for ripeness. Therefore, fruits grading in present study only considers the colour of the skin of the bananas.The method that is used to develop this BGS is image processing method in term of color histogram of RGB.The color histogram method is evaluating the mean value of red, green and blue in order to classify the banana.In this BGS, fifty sample of banana is tested.From the result,the successful rate of grading the banana is 85% percent while the error rate is 15% percent.,based on the objective of this system which is to develop grading system to judge the maturity level and to standardize the banana grading based on maturity level, the objective is successfully achieved the goal.The problem regarding grading system by using Human Visualization System also solved.The cost of manual grading system,the time for grading the bananas and the man power uses is decreased.